2007
DOI: 10.1039/b617552j
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of efficient electron–hole separation in TiO2nanoparticles revealed by femtosecond transient absorption spectroscopy under the weak-excitation condition

Abstract: The transient absorption of nanocrystalline TiO(2) films in the visible and IR wavelength regions was measured under the weak-excitation condition, where the second-order electron-hole recombination process can be ignored. The intrinsic dynamics of the electron-hole pairs in the femtosecond to picosecond time range was elucidated. Surface-trapped electrons and surface-trapped holes were generated within approximately 200 fs (time resolution). Surface-trapped electrons, which gave an absorption peak at around 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

39
330
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(372 citation statements)
references
References 54 publications
39
330
0
3
Order By: Relevance
“…3 and 4, charge scavenging by interacting gases, which typically occurs on the nanosecond-microsecond time scale, is not expected to dominate. Instead, the majority of the transient signal decay in this time regime (<500 ps) is likely due to recombination and relaxation of charge carriers into deeper trap states (45).…”
Section: Resultsmentioning
confidence: 99%
“…3 and 4, charge scavenging by interacting gases, which typically occurs on the nanosecond-microsecond time scale, is not expected to dominate. Instead, the majority of the transient signal decay in this time regime (<500 ps) is likely due to recombination and relaxation of charge carriers into deeper trap states (45).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of TiO 2 , surface-trapped electrons and holes are generated within 200 fs after photoexcitation [10]. Surface-trapped and bulk electrons equilibrate and relax into deep trap sites with a time constant of a few hundred picoseconds [10].…”
Section: Timescale Of Photocatalysismentioning
confidence: 99%
“…In the case of TiO 2 , surface-trapped electrons and holes are generated within 200 fs after photoexcitation [10]. Surface-trapped and bulk electrons equilibrate and relax into deep trap sites with a time constant of a few hundred picoseconds [10]. Photoexcited electrons react with gaseous O 2 within 10-100 ls [11], whereas surface-trapped holes react with methanol, ethanol, and 2-propanol within 300, 1000, and 3000 ps, respectively [12].…”
Section: Timescale Of Photocatalysismentioning
confidence: 99%
See 1 more Smart Citation
“…To date, results of studies on the carrier relaxation dynamics in TiO 2 are sparsely presented in literature. By using the method of transient absorption spectroscopy, Tamaki et al 44 reported on the capture of free electrons into trap states at the semiconductor surface, occurring on a time scale of ∼ 200 fs.…”
Section: Injection Kineticsmentioning
confidence: 99%